1999
DOI: 10.1073/pnas.96.15.8768
|View full text |Cite
|
Sign up to set email alerts
|

Targeted manipulation of maize genes in vivo using chimeric RNA/DNA oligonucleotides

Abstract: Site-specific heritable mutations in maize genes were engineered by introducing chimeric RNA͞DNA oligonucleotides. Two independent targets within the endogenous maize acetohydroxyacid synthase gene sequence were modified in a site-specific fashion, thereby conferring resistance to either imidazolinone or sulfonylurea herbicides. Similarly, an engineered green f luorescence protein transgene was site-specifically modified in vivo. Expression of the introduced inactive green f luorescence protein was restored, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 34 publications
1
131
1
2
Order By: Relevance
“…In consequence, OMM should lead to fewer unintended effects. The high specificity of the technique has been demonstrated in several studies, and the risk of potential unwanted mutagenesis has been shown to be very low when the oligonucleotide structure and chemistry were properly designed (Agarwal et al, 2003;Beetham et al, 1999;Kochevenko and Willmitzer, 2003;Okuzaki and Toriyama, 2004;Zhu et al, 1999Zhu et al, , 2000. Altered genes have also been shown to be heritable and stable, at least in plants (see Sect.…”
Section: Safety Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In consequence, OMM should lead to fewer unintended effects. The high specificity of the technique has been demonstrated in several studies, and the risk of potential unwanted mutagenesis has been shown to be very low when the oligonucleotide structure and chemistry were properly designed (Agarwal et al, 2003;Beetham et al, 1999;Kochevenko and Willmitzer, 2003;Okuzaki and Toriyama, 2004;Zhu et al, 1999Zhu et al, , 2000. Altered genes have also been shown to be heritable and stable, at least in plants (see Sect.…”
Section: Safety Issuesmentioning
confidence: 99%
“…Although the usefulness of the technique has been first demonstrated in mammalian cells, preliminary studies at the end of the nineties have shown that oligonucleotidemediated mutagenesis is applicable to plants and can induce target gene mutations (Beetham et al, 1999;Gamper et al, 2000;Hohn and Puchta, 1999;Zhu et al, 1999). Successful in vivo gene modification has been demonstrated notably in maize, rice, tobacco and wheat, e.g.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimeraplasty has been showed in bacteria, 133 and yeast 146 as well as in vitro and in vivo in a wide variety of target cells and tissues, including skin melanocytes, 139,147 kidney, 148,149 and the skeletal muscle in both dog 150 and mouse 151,152 models of Duchenne muscular dystrophy as well as plants. [153][154][155] These numerous studies have established correction by showing phenotypic and non-PCRbased genotypic correction both in cultured cells and in vivo.…”
Section: Gene Repair Strategiesmentioning
confidence: 99%
“…The tandem development of transgenic knockout populations, transposon insertions, chemical gene machines, and the genotyping of single nucleotide polymorphisms within large populations have paved the way to a far more substantial base of genetic diversity than imagined a few years ago (Aarts et al, 1993;Schaefer and Zryd, 1997;Strepp et al, 1998;Cho et al, 1999;Zu et al, 1999). That these developments have occurred in parallel with both the elucidation of complete genomes of several organisms and the rapid development of multiparallel technologies to describe properties of the biological systems (for review, see Celis et al, 2000) has provided the driving force behind many genomics initiatives.…”
mentioning
confidence: 99%